INSIGHTS FROM THE LEGISLATIVE BRANCH: FELLOW EXPERIENCES IN LEGISLATIVE OFFICES AND COMMITTEES. (11th November 2018) - Lewinson, T; Castro, C; Hallarman, L; Riser, T; Batchelor-Murphy, M
Abstract: Dr. Lewinson will summarize the collected insights and opinions related to health and aging of Fellows from placements in the congressional offices of Representatives from Georgia and Texas, the Senate Special Committee on Aging, the Senate Finance Committee, and the Congressional Research Service. Special attention will be paid to the priorities of these legislative entities and the opportunities and barriers they encounter. Topics covered will include Older American's Act reauthorization, housing and poverty, Alzheimer's disease and dementia care, and the opioid crisis.